Upaya Pencegahan Anemia Pada Ibu Hamil Melalui Edukasi dan Pemberian Biskuit Ibu Hamil di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2025 - Ariska Fauzianty; Friza Novita Sari Situmorang; Damayanti Damayanti; Khairunnisa Khairunnisa; Nova Isabella Mariance Br Napitupulu; Humaida Hanim; Plora Novita Febrina Sinaga; Yasrida Nadeak; Polmaria Panjaitan; Hadisyah Hadisyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Globally, the prevalence of anemia in pregnant women in 2019 was 35.6%. The prevalence of anemia in developing countries is relatively high, such as Southeast Asia at 47.8%, compared to developed countries such as America at 18.9%. Efforts that can be made to prevent anemia include education, giving pregnant women biscuits and giving Fe tablets. This activity was carried out at the Bangun Rejo Village Health Center, Dusun VII, Tanjung Morawa District. The method used in this service is to provide education directly to pregnant women at the Bangun Rejo Village Health Center. The results of this activity were carried out in stages starting from preparation to evaluation. After implementing health education, giving pregnant women biscuits and giving Fe tablets, there was an increase in knowledge and consumption of Fe. Therefore, with this community service project, it is hoped that all pregnant women can increase awareness and Fulfill nutrition and balanced nutrition, regularly consume Fe tablets.